Anti-inflammatory effect of curcumin on neurological disorders: a narrative review - Zhou, Baoyin; Hu, Binbin (Frontiers in Pharmacology, 2025)
Neuroinflammation arises from the synergistic interplay of multiple inflammatory mediators and is pathologically associated with various neurological disorders. These conditions are complex, multifactorial diseases characterized by dynamic interactions between chronic neuroinflammation, oxidative stress, and progressive neuronal degeneration. Curcumin, a naturally occurring polyphenolic compound, exhibits significant pharmacological activity in anti-inflammatory processes and immune regulation. Within neuroinflammatory pathologies, microglial cells are crucial effector cells as they can secrete inflammatory mediators. Emerging evidence suggests that these resident immune cells are the primary site of the biological activity of curcumin in the central nervous system. The compound demonstrates multimodal regulatory effects, including modulation of key signaling pathways (NF-κB, NLRP3 inflammasome, and Nrf2) and upregulation of anti-inflammatory cytokines (TGF-β and interleukin-10), collectively contributing to the neuroinflammatory suppression effect of curcumin. This review comprehensively analyzed the therapeutic potential of curcumin in neuroinflammation and explored its clinical prospects for neurological disease intervention.